Lulur Daun Pegagan Sebagai Perawatan Badan Untuk Mengatasi Stretch Mark - Nurulisma Saputri; Sefira Maharani; Sofia Daniati (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2022)
The onset of stretch Marks makes some people feel insecure. The author made a scrub made from gotu kola leaves. This study aims to determine how to make scrub leaves gotu kola, knowing the feasibility sensory test and knowing the condition of stretch marks after using scrub leaves gotu kola. This study was conducted by observation, interviews, questionnaires, experiments, documentation, and literature. The analysis used qualitative descriptive analysis. The manufacture of powder starts from the preparation of tools and materials, washing, weighing, drying, rarefaction, weighing dry leaves. The powder is taken to taste and mixed using olive oil. The product results are submitted to five expert validators to test the feasibility of the product using sensory tests. The feasibility of the product was tested by color averaging 4,7 in the very decent category, aroma averaging 4,1 in the decent category, texture averaging 4,1 in the decent category, ease of use averaging 3,9 in the moderately decent category, packaging averaging 4,9 in the very decent category. There is an improvement in the product that is more mashed powder, mixing powder using warm water and olive oil in a ratio of 1:2 and cooling scrub enough 5-10 minutes. Based on the results of the feasibility of the product can be concluded concluded that the product scrub leaves gotu kola feasible to be a new innovation in the manufacture of scrubs. The use of scrubs for 6 times conducted by 10 respondents resulted in the condition of stretch marks that fade, skin texture becomes more flat and the stretch decreases.